HUBUNGAN BEBAN KERJA DENGAN WAKTU TANGGAP PERAWAT GAWAT DARURAT MENURUT PERSEPSI PASIEN DI INSTALASI GAWAT DARURAT RSU PANDAN ARANG BOYOLALI - Widodo, Panggah; Pratiwi, Arum (Jurnal Berita Ilmu Keperawatan, 2008)
Background : Service of emergency patient is needed quick, right,and responsive to prevent immortality and disability. One of quality serviceindication is time response. Patient entering to Emergency Room cannot be guessed their condition, time and amount. Average patients on every shift a year is 18 patients. There is an appropriate number of nurses between situation and condition. While nursing on Emergency Room, nurses have also taken care patients on hospitalization installation capacity 13 patients. Emergency Room nurses always get complaints that there is a slow service on emergency room. Whereas, the researcher want to know the relation between job duty with emergency nurse’s time response based on patient perception on Emergency Room of Pandan Arang general hospital Boyolali Method: This research use correlation model with cross sectional. Sample for variable job duty is 16 nurses, taken by total sampling technique. Sample for time variable nurse response according to patients perceptions are 16 patients, taken by purposive sampling technique. A patient had taken service of nurse values that a nurse using questionnaires. Data collected is the analysis by using statistic test Product Moment. Conclusion: Result of the study shows that (1) Nurses’ job duty of Emergency Room is categorized hard. (2) Time response emergency nurses according to patients’ perception is slow and quickly. (3) There is a relationship between physical job duty with nurses’ time response of Emergency Room. (4) There is no relationship between psychological job duty with nurses’ time response of Emergency Room. (5) There is no relationship between social job duty with nurses’ time response of Emergency Room. (6) There is no relationship between totality job duty (physical, psychology and social) with nurses’ time response of Emergency Room according to patients’ perception on emergency room of Pandan Arang general hospital Boyolali